2020
DOI: 10.1177/1462474519899949
|View full text |Cite
|
Sign up to set email alerts
|

Polluting our prisons? An examination of Oklahoma prison locations and toxic releases, 2011–2017

Abstract: Recent research has highlighted numerous environmental concerns with US prisons, including that prisons are often located on undesirable land that is in close proximity to environmental hazards. We utilize an environmental justice and green criminology perspective to test this in Oklahoma using data on prison sites and toxic releases provided by the US Environmental Protection Agency for a period of seven years (2011–2017). We focus on Oklahoma because it recently became the state with the highest overall inca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 50 publications
(112 reference statements)
1
32
0
Order By: Relevance
“…Accordingly, the goal of this study is to examine patterns of toxic releases in areas with and without prison facilities. Towards this goal, this study will provide a direct response to Bradshaw’s (2018) call for the bridging of prison-based scholarship and green criminology and expand upon the work of Leon-Corwin and colleagues (2020) by examining zip-code level emissions across the U.S. to determine the role (if any) of prison locations. Two research questions will be explored: Research Question 1: Across the U.S., is the location of a prison in a zip code associated with higher toxic releases? Research Question 2: Does any identified pattern hold across all regions of the U.S.? …”
Section: This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the goal of this study is to examine patterns of toxic releases in areas with and without prison facilities. Towards this goal, this study will provide a direct response to Bradshaw’s (2018) call for the bridging of prison-based scholarship and green criminology and expand upon the work of Leon-Corwin and colleagues (2020) by examining zip-code level emissions across the U.S. to determine the role (if any) of prison locations. Two research questions will be explored: Research Question 1: Across the U.S., is the location of a prison in a zip code associated with higher toxic releases? Research Question 2: Does any identified pattern hold across all regions of the U.S.? …”
Section: This Studymentioning
confidence: 99%
“…Yet, prisons are in some cases disproportionately located in areas fraught with environmental hazards and toxic waste (Abolitionist Law Center and Human Rights Coalition, 2014; Bradshaw, 2018; Leon-Corwin et al, 2020; Norton and Schept, 2019; Schept, 2022). A comprehensive study of facilities emitting toxic waste in Oklahoma, for example, identified proximity to a prison as a salient predictor of elevated toxic emission levels (Leon-Corwin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These areas are composed of institutions like prisons, in which people may have increased vulnerability to environmental pollution, which would limit the potential applicability of the NEVI in those areas. 54,55 Additionally, we have currently only used the NEVI in one large, diverse, and densely populated urban center, potentially limiting the generalizability of patterns in domains of potential vulnerability to other urban areas. However, the adaptable process of creating the NEVI would facilitate the creation and comparison of the index in other urban areas to ascertain their distinct patterns of potential vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…This method was employed by the first major US EJ study on air pollution . Since then, it continues to be used as a simple and widely recognized means of capturing the detrimental effects of living close to environmental hazards. , UHC is typically used in studies concerned with hazardous air pollutants (HAPs) from industrial sources or other point source pollution. Toxic release locations are often the input data of proxy methods because of the detrimental health effects of living close to industry and infrastructure.…”
Section: Review Of Common Modeling and Data Analytic Techniques To Cr...mentioning
confidence: 99%